Zasada zrównoważonego rozwoju w turystyce - Dominika Dzwonkowska (Studia Ecologiae et Bioethicae)
Tourism has become one of the most popular leisure activities and the number of tourists has increased remarkably in recent years. UNWTO forecasts further development of this sector, predicting that the number of international arrivals will reach nearly 1.6 billion by the year 2020. Growth in the number of tourists poses a serious threat to the environment. The way to solve this problem is by introducing a more sustainable approach to this sector. The concept of sustainability was recently introduced into tourism and we can already notice many good practices. The article focuses on presenting the concept of sustainable tourism, its key objectives, and main characteristics, cases of its application, challenges connected with a more sustainable approach to tourism. Sustainable tourism is presented as the solution for environmental and social problems caused by intensified tourist activity.